Imaging single barium atoms in solid xenon for barium tagging in the nEXO neutrinoless double beta decay experiment - Walton, Timothy, author; Fairbank, William M., advisor; Berger, Bruce, committee member; Van Orden, Alan, committee member; Wilson, Robert, committee member (Colorado State University. Libraries, 2016)
The nEXO experiment will search for neutrinoless double beta decay of the isotope 136Xe in a ton-scale liquid xenon time projection chamber, in order to probe the Majorana nature of neutrinos. Detecting the daughter 136Ba of double beta decay events, called barium tagging, is a technique under investigation which would provide a veto for a background-free measurement. This would involve detecting a single barium ion from within a macroscopic volume of liquid xenon. One proposed barium tagging method is to trap the barium ion in solid xenon at the end of a cold probe, and then detect it by its fluorescence in the solid xenon. In this thesis, new studies on the spectroscopy of deposits of Ba and Ba+ in solid xenon are presented. Imaging of barium atoms in solid xenon is demonstrated with sensitivity down to the single atom level. Achievement of this level of sensitivity is a major step toward barium tagging by this method.